Network Pharmacology and Molecular Docking on the Molecular Mechanism of Luo-hua-zi-zhu (LHZZ) Granule in the Prevention and Treatment of Bowel Precancerous Lesions - Cui Guo; Cui Guo; Xingdong Kang; Fang Cao; Jian Yang; Yimin Xu; Xiaoqiang Liu; Xiaoqiang Liu; Yuan Li; Xiumei Ma; Xiaoling Fu (Frontiers Media S.A., 2021)
The Luo-hua-zi-zhu (LHZZ) granule has been widely used for the treatment of colorectal adenoma (CRA), which is a precursor of colorectal cancer (CRC). However, the active components of LUZZ and its mechanism of action against CRA have not yet been elucidated. This study was designed to investigate the effect of LHZZ on CRA and explore its pharmacological mechanisms. First, a total of 24 chemical constituents were identified in the 50% aqueous methanol extract of LHZZ granule based on the mass fragment patterns and mass spectral library using the high resolution UPLC-Q-TOF MS/MS system. Subsequently, based on a network pharmacology study, 16 bioactive compounds and 28 targets of the LHZZ associated with CRA were obtained, forming a compound-target network. Molecular docking tests showed tight docking of these compounds with predicted targeted proteins. The protein-protein interaction (PPI) network identified AKT1, CASP3, TP53 and EGFR as hub targets. The Kyoto Encyclopedia of Genes and Genomes pathway network and pathway-target-compound network revealed that the apoptosis pathway was enriched by multiple signaling pathways and multiple targets, including the hub targets. Finally, the reliability of the core targets was evaluated using molecular docking technology and in vitro studies. Our study indicated that the LHZZ particle has preventive and treatment effect on colorectal adenoma through multi-component, multi-target and multi-pathway.